The Agentic Belonging Workshop: A Quasi-Experimental Evaluation of a Social Belonging Intervention in two English Universities - David Gilani; Daniel McArthur; Liz Thomas (Student Success)
Given its close links to student success, universities are heavily invested in how they can positively influence their students’ sense of belonging. One approach to this is through social belonging interventions, where universities attempt to develop student agency. This study takes a quasi-experimental approach by evaluating the impact of a newly developed agentic belonging workshop at two English universities. One hundred and one first-year undergraduate students attended either this belonging workshop (36), a control study-skills workshop (27), or they attended neither workshop (38). Findings show that the agentic workshop led to significantly higher self-reported scores in understanding of belonging amongst attendees compared to non-attendees. Whilst changes in students’ sense of belonging was not significantly different across workshop groups, belonging workshop attendees were significantly more likely to continue into the second year of study compared to both control groups. This study contributes promising findings for how social belonging interventions can be taken forward within the higher education context in the United Kingdom.